A review: digital stereo close range videogrammetry for three dimensional measurements - Ibrahim, Mohd. Sharuddin; Setan, Halim; Chong, Albert K. (2006)
Usually photogrammetrist used still image for measurement and modeling of object. Videogrametry refers to video images taken using camcorder or movie function on digital still camera. Video movie consists of sequences of images (or frames). If video speed is 25 fps (frame per second) and taken for 1 minute (i.e. 60 seconds), there are 25 frame per second or overall 1500 image. This paper highlights the capabilities of video as a tool for 3D measurement and modeling, as well as still image. Several advantages are discusses in detail. This paper discusses an on-going research to develop a real time video capturing software and procedure for high-accuracy real-time data capture and image analysis. The development also focuses on the optimization, in terms of method, procedure, low-cost and accurate results. The research methodology consists of real time video capturing, image analysis, bundle adjustment, motion detection, motion tracking and 3 D coordinate movement on each frame. With this development, it can be applied to measure moving object such as sport analysis, metrology, inspection, and model the motion of human for medical purposes.